Nerve growth factor sensitizes nociceptors to C-fibre selective supra-threshold electrical stimuli in human skin - Schnakenberg, Mark; Thomas, Christian; Schmelz, Martin; Rukwied, Roman (European journal of pain, 2021)
Background Intradermal injection of 1 µg nerve growth factor (NGF) causes sustained nociceptor sensitization. Slowly depolarizing electrical current preferentially activates C-nociceptors. Methods We explored the differential contribution of A-delta and C-nociceptors in NGF-sensitized skin using slowly depolarizing transcutaneous electrical current stimuli, CO2 laser heat, mechanical impact, and A-fibre compression block. In 14 healthy volunteers, pain rating was recorded on a numeric scale at days 1-14 after NGF treatment. Ratings during A-fibre conduction block were investigated at days 3 and 7 post-NGF. Results Pain ratings to electrical, CO2 heat and mechanical impact stimuli were enhanced (>30%, p < .0005, ANOVA) at NGF-injection sites. Axon reflex erythema evoked by electrical stimulation was also larger at NGF-injection sites (p < .02, ANOVA). Diminution of pain during continuous (1 min) sinusoidal current stimulation at 4 Hz was less pronounced after NGF (p < .05, ANOVA). Pain ratings to electrical sinusoidal and mechanical impact stimuli during A-fibre conduction block were significantly elevated at the NGF sites compared to NaCl-treated skin (p < .05, ANOVA). Conclusions NGF-induced sensitization of human skin to electrical and mechanical stimuli is primarily driven by C-nociceptors with little contribution from A-delta fibres. Less-pronounced accommodation during ongoing sinusoidal stimulation suggests that NGF could facilitate axonal spike generation and conduction in primary afferent nociceptors in humans. Further studies using this sinusoidal electrical stimulation profile to investigate patients with chronic inflammatory pain may allow localized assessment of skin C-nociceptors and their putative excitability changes under pathologic conditions. Significance The application of novel slowly depolarizing electrical stimuli demonstrated a predominant C-nociceptor sensitization in NGF-treated skin. Increased pain ratings, larger axon reflex erythema and less accommodation of C-fibres to ongoing sinusoidal stimulation all indicated an enhanced nociceptor discharge after NGF. A-fibre conduction block had little effect on electrical and mechanical hyperalgesia skin in NGF-treated compared to NaCl-treated skin. This electrical stimulus profile may be applicable for patients with chronic inflammatory pain, allowing localized assessment of skin C-nociceptors and their putative excitability changes under pathologic conditions.
Gesehen am 01.07.2021
First published: 16 October 2020